2016
DOI: 10.1097/bsd.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nutritional Status as an Adjunct Predictor of Major Postoperative Complications Following Anterior Cervical Discectomy and Fusion

Abstract: In this analysis of a prospective surgical outcomes database, preoperative serum hypoalbuminemia was an important adjunct predictor of major complications following ACDF. In high-risk patients with multiple medical comorbidities, we recommend that clinicians consider nutritional screening and optimization as part of preoperative risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Our study found that obesity was a significant predictor of surgical site complications in orthopaedic trauma patients with high-energy injuries. This is in line with the experience of elective orthopaedic procedures that have reported similar results [10][11][12][13][14][15] . Our data emphasizes the urgent need for proper assessment of malnutrition in orthopaedic trauma patients during the early treatment phase.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study found that obesity was a significant predictor of surgical site complications in orthopaedic trauma patients with high-energy injuries. This is in line with the experience of elective orthopaedic procedures that have reported similar results [10][11][12][13][14][15] . Our data emphasizes the urgent need for proper assessment of malnutrition in orthopaedic trauma patients during the early treatment phase.…”
Section: Discussionsupporting
confidence: 88%
“…Malnutrition as a risk factor for poor outcomes has been well established in the medicine literature [1][2][3][4][5][6] as well as the general surgery literature [7][8][9] . Within the field of orthopaedic surgery, hypoalbuminemia and obesity have been reported as significant risk factor for adverse outcomes in elective procedures, such as arthroplasty and spinal fusions [10][11][12][13][14][15] ,. Data from the literature on malnutrition in orthopaedic trauma patients remains scarce and is mostly limited to studies in elderly patients undergoing hip fracture surgery [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, orthopedic surgeons are becoming increasingly aware of the importance of nutritional status prior to elective surgery [9,18,22,27]. To define malnutrition, most surgeons use serum laboratory values such as albumin concentration and total lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…Underweight is a measure of malnutrition, which has been associated with increased risk of infections, numerous medical complications, and death in surgical patients. [16][17][18] The nutritional demands of children in appropriate wound healing and recovery after operative intervention are fundamental in preventing short-term complications. Concurrently, obesity in children has been linked to surgical site infections, thromboembolic events, and decubitus ulcers.…”
Section: Discussionmentioning
confidence: 99%